THE EFFECTS OF VITAMIN D SUPPLEMENTATION ON DISEASE ACTIVITY IN SYSTEMIC LUPUS ERYTHEMATHOSUS PATIENTS: AN EVIDENCE-BASED CASE REPORT - Faridahanum, Santri Dwizamzami; Steffi Sonia (Perhimpunan Dokter Gizi Klinik Indonesia, 2026)
Background: Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease characterized by the production of autoantibodies and multisystem involvement, predominantly affecting women of reproductive age. Vitamin D is known to have immunomodulatory effects, including inhibition of T and B cell activation and suppression of pro-inflammatory cytokine production. Objectives: This evidence-based case report aims to evaluate the effect of vitamin D supplementation on disease activity in SLE. Methods: A literature search was conducted using PubMed, Scopus, and Cochrane. Medical Subject Headings (MeSH) terms and relevant keywords based on the clinical question components were applied. All retrieved literature was screened using predefined eligibility criteria, followed by a critical appraisal of eligible studies. Results: One meta-analysis of randomized controlled trials (RCTs) and two RCTs met the eligibility criteria. Almost all of the included studies recruited patients with SLE who had vitamin D deficiency/insuficiency. The methodological validity of all three studies was considered acceptable. The studies demonstrated heterogeneity in terms of baseline disease activity levels among their study populations. The meta-analysis and one of the RCTs reported non-significant results, while the other RCT showed a significant improvement in disease activity following vitamin D supplementation. Conclusion: Current evidence is insufficient to recommend vitamin D supplementation as an adjuvant therapy for improving disease activity in patients with SLE and further research is needed.